Efficacy and safety of abaloparatide for the treatment of post-menopausal osteoporosis. (3rd May 2019) - Merlotti, D.; Falchetti, A.; Chiodini, I.; Gennari, L.
ABSTRACT: Introduction : Osteoporosis is a skeletal disorder characterized by loss of bone mass and strength affecting up to 30–50% of postmenopausal women worldwide. Current therapeutic options include antiresorptives such as aminobisphosphonates or denosumab and osteoanabolic compounds such as teriparatide. Areas covered : In this review, the authors summarize the clinical development, safety and efficacy profile of abaloparatide, a new osteoanabolic agent recently marketed in the US for the treatment of postmenopausal osteoporosis in women who are at high risk for fracture or who fail antiresorptive therapy. Expert opinion : Abaloparatide is a 1-34 PTH related peptide-like molecule that has been modified in order to potentiate the osteoanabolic effect. In its pivotal phase 3 trial in postmenopausal women with osteoporosis, subcutaneous abaloparatide 80 mcg/day reduced the risk of vertebral, nonvertebral, major osteoporotic, and clinical fractures compared with placebo and reduced the risk of major osteoporotic fractures compared with teriparatide. These results, together with a reduced prevalence of hypercalcemia and a lower cost of the marketed compound, point toward improved cost effectiveness with abaloparatide versus teriparatide. However, some concerns have been raised due to a somewhat higher occurrence of adverse effects (particularly with palpitations and increased heart rate) or the resultant discontinuation due to these adverse effects when compared to teriparatide.